PILIHAN METODE PENELITIAN KUANTITATIF DALAM BIDANG PENDIDIKAN - HENDAYANI, METI (Tsamratul Fikri | Jurnal Studi Islam, 2018)
In education, research is very important in order to find new theories that are more effective, efficient for the renewal of education in accordance with the changing times, as well as answering some issues related to education. Basically research is a systematic activity or process to solve problems that are done by applying scientific method that aims to explain, predict or control the phenomenon in accordance with the steps that have been arranged correctly and mutually support each other. In the research required research methods that will be used later. One of the research methods used in the scope of education is quantitative research. Quantitative method is also called the discovery method, because with this method can be found and developed a variety of new science and technology, and if the hypothesis is accepted it will contribute to intellectual property. Quantitative research method is a research method to test a particular theory that has been by examining the relationship between variables. The variables in this quantitative research are measured using a research instrument which then the data of the research results are analyzed in accordance with statistical procedures. This study attempts to reduce observational errors through experimental or correlative design to arrive at conclusions and try to deepen and break through its symptoms by interpreting problems or concluding the mix of different meanings of problems as presented by the situation.